TEXTOS QUE VUELAN: PRODUCCIÓN Y TRAYECTORIAS DE REPORTES ESCRITOS SOBRE LA MIGRACIÓN DE LA MARIPOSA MONARCA. - Méndez-Arreola, Roberto; Kalman, Judith (Trabalhos em Lingüística Aplicada)
For the most part, the scientific and research community assesses the texts written by participants in citizen science programs on the criteria of reliability and scientific validity, often invalidating the contextual nature of their writing. Using an ethnographic perspective and guidelines of New Literacy Studies, we analyze the production processes and textual trajectories of reports written by two contributors in a citizen science program that monitors the migration of the monarch butterfly in Mexico. We pay attention to the ways they produce their texts, the material and linguistic resources they use, the way they construct their writings, and their ideas about the production of written documents. We reconstruct the trajectory of each text by following them through their production process, their place in the social activities that the authors participate in when creating them, the way the writers transport and modify their writing from one context to another. Through the categories of ideal texts, bridge texts, and global texts, we show that the normative speech of research and scientific knowledge plays a vital role in their production and trajectory (Gee, 2007) and that consequently impacts how participants write about the migration of the monarch butterfly.